2014
DOI: 10.1371/journal.pone.0091592
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Bi-Layer Silk Fibroin Scaffolds Support Tissue Regeneration in a Rabbit Model of Onlay Urethroplasty

Abstract: Acellular scaffolds derived from Bombyx mori silk fibroin were investigated for their ability to support functional tissue regeneration in a rabbit model of urethra repair. A bi-layer silk fibroin matrix was fabricated by a solvent-casting/salt leaching process in combination with silk fibroin film casting to generate porous foams buttressed by homogeneous silk fibroin films. Ventral onlay urethroplasty was performed with silk fibroin grafts (Group 1, N = 4) (Width×Length, 1×2 cm2) in adult male rabbits for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 42 publications
3
59
1
Order By: Relevance
“…Since sericin may have a stronger immunogenicity, silk fibroin [4][5][6][7][8][9][10][11][12][13][14][15] or degummed raw silk [17][18][19] is used in biomedical research. In this study, raw silk and degummed raw silk were implanted subcutaneously into ten Sprague-Dawley rats.…”
Section: Immunogenicity Of Sericinmentioning
confidence: 99%
See 2 more Smart Citations
“…Since sericin may have a stronger immunogenicity, silk fibroin [4][5][6][7][8][9][10][11][12][13][14][15] or degummed raw silk [17][18][19] is used in biomedical research. In this study, raw silk and degummed raw silk were implanted subcutaneously into ten Sprague-Dawley rats.…”
Section: Immunogenicity Of Sericinmentioning
confidence: 99%
“…In the degradation process, cells play a significant role in both the in vitro and in vivo environments [13,20,25]. At present, only a few studies have focused directly on investigating the degradation mechanism of the materials or the role tissue solution and cells play during the in vivo degradation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk fibroin (SF) is a novel protein obtained from Bombyx mori cocoons that have good biocompatibility and low immunogenicity [26,27]. The mechanical property and microstructure of was improved after it was stretched in 90% ethanol [28].…”
Section: Protein Derived Scaffolds and Cellulosementioning
confidence: 99%
“…The mechanical property and microstructure of was improved after it was stretched in 90% ethanol [28]. Both accellular and cell seeded SF showed good efficacy in urethral reconstruction in animal model [26,29,30]. Recently, Lv et al [31] reported a novel oxygen-generating material composed of SF, keratin, calcium peroxide and gelatin.…”
Section: Protein Derived Scaffolds and Cellulosementioning
confidence: 99%